Blood Pressure and Adverse Events During Continuous Flow Left Ventricular Assist Device Support. (May 2015) - Saeed, Omar; Jermyn, Rita; Kargoli, Faraj; Madan, Shivank; Mannem, Santhosh; Gunda, Sampath; Nucci, Cecilia; Farooqui, Sarah; Hassan, Syed; Mclarty, Allison; Bloom, Michelle; Zolty, Ronald; et al.
<x xml:space="preserve">Abstract</x> Background— Adverse events (AEs), such as intracranial hemorrhage, thromboembolic event, and progressive aortic insufficiency, create substantial morbidity and mortality during continuous flow left ventricular assist device support yet their relation to blood pressure control is underexplored. Methods and Results— A multicenter retrospective review of patients supported for at least 30 days and ⩽18 months by a continuous flow left ventricular assist device from June 2006 to December 2013 was conducted. All outpatient Doppler blood pressure (DOPBP) recordings were averaged up to the time of intracranial hemorrhage, thromboembolic event, or progressive aortic insufficiency. DOPBP was analyzed as a categorical variable grouped as high (>90 mm Hg; n=40), intermediate (80–90 mm Hg; n=52), and controlled (<80 mm Hg; n=31). Cumulative survival free from an AE was calculated using Kaplan–Meier curves and Cox hazard ratios were derived. Patients in the high DOPBP group had worse baseline renal function, lower angiotensin-converting enzyme inhibitor or angiotensin receptor blocker usage during continuous flow left ventricular assist device support, and a more prevalent history of hypertension. Twelve (30%) patients in the high DOPBP group had an AE, in comparison with 7 (13%) patients in the intermediate DOPBP group and only 1 (3%) in the controlled DOPBP group. The likelihood of an AE increased in patients with a high DOPBP (adjusted hazard ratios [95% confidence interval], 16.4 [1.8–147.3]; P=0.012 versus controlled and 2.6 [0.93–7.4]; P=0.068 versus intermediate). Overall, a similar association was noted for the risk of intracranial hemorrhage (P=0.015) and progressive aortic insufficiency (P=0.078) but not for thromboembolic event (P=0.638). Patients with an AE had a higher DOPBP (90±10 mm Hg) in comparison with those without an AE (85±10 mm Hg; P=0.05). Conclusions— In a population at risk, higher DOPBP during continuous flow left ventricular assist device support was significantly associated with a composite of AEs.